Genome-Wide Characterization, Evolution and Expression Profiling of the UDP-Glycosyltransferase Family in Grapes (Vitis vinifera) - WANG Yuanyuan, LIU Yunqing, XU Jingyu, LIU Yunting, HU Xixi, ZHANG Chao, JIANG Zeyu, ZHU Lei (Shipin Kexue, 2025)
In order to fully understand the basic information of the UDP-glucosyltransferase gene (VvUGT) family in grapes and to select candidate UGT genes that regulate anthocyanin biosynthesis in Vitis amurensis, the bioinformatics analysis of the VvUGT family was carried out by genome-wide identification, physicochemical properties determination, phylogenetic evolution, chromosome location, gene structure and motif characterization of VvUGT, and the expression analysis of VvUGT was carried out based on the Gene Expression Omnibus (GEO) database (GSE36128). The skins of three grape varieties (‘Zuoshanyi’ ‘Zuohongyi’ and ‘Cabernet Sauvignon’) with different genetic backgrounds were selected for analysis of their anthocyanin and VvUGT expression during the veraison period, and VvUGT involved in anthocyanin accumulation in Vitis amurensis was preliminarily selected. The results showed that the grape UGT family contained 230 members, which were divided into 16 groups (A–P). The protein members were mainly distributed in the chloroplast, nucleus and cytoplasm. The genes were distributed on 18 chromosomes except chr10. The number of introns in the genes in this family ranged from 1 to 6, and all genes contained PSPG structure. The expression of VvUGT in V. vinifera ‘Corvina’ was tissue specific and spatiotemporally specific. Anthocyanin contents and glycosylated anthocyanin composition were significantly different among the three grape varieties. Transcriptome analysis showed that the expression patterns of 85 VvUGT genes with high expression levels during the veraison process showed significant differences between varieties and growth periods. Correlation analysis suggested that Vitvi15g01073.t01, Vitvi15g01643.t01 and Vitvi17g00753.t01 (5GT) might play a critical role in the anthocyanin biosynthesis in V. amurensis. This study provides a theoretical basis for understanding the function of candidate genes in the anthocyanin synthesis of V. amurensis, and lays a foundation for the varietal improvement of V. amurensis varieties and the enhancement of the color stability of V. amurensis wine.